ECOLOGICAL EDUCATION IN THE PERSPECTIVE OF THE QUR’AN: ISLAMIC SOLUTIONS TO ENVIRONMENTAL CRISIS AND CLIMATE CHANGE - Mardan; Moge, Romi; Achmad Abubakar (LP2M IAIN Sultan Amai Gorontalo, 2025)
The phenomenon of ecological damage and climate change has developed into a multidimensional crisis that threatens the sustainability of human life on earth. This crisis is not only ecological, but also reflects a moral and spiritual crisis due to the loss of human awareness of the Divine mandate in preserving nature. This research aims to examine the concept of ecological education in the perspective of the Qur'an as an Islamic solution to the global environmental crisis. The focus of research is directed at the values of monotheism, the principle of balance (mīzān), and the prohibition of damage (fasād) as the basis for the development of ecological awareness oriented towards responsibility and sustainability.Using a qualitative approach based on thematic interpretation (maudhu'i), this study analyzes the verses of the Qur'an that discuss the earth (ardh) and the relationship between humans and nature. The results of the study show that the Qur'an places the earth as a Divine mandate that must be maintained through the principles of responsibility, balance, and sustainability. These findings led to the construction of a Qur'anic ecological education model that emphasizes the spiritual and ethical dimensions in human interaction with the environment. The implications of the study affirm the importance of integrating ecotheological education into the Islamic curriculum as well as the formulation of global environmental policies based on Qur'anic values as a preventive step in dealing with contemporary ecological crises.